A fração de acetado de etila de bixa orellana e seu composto isolado ácido elágico atenuam a progressão da osteoartrite induzida por MIA em joelhos de ratos - SANTIAGO, Luis Ângelo Macedo (2023)
Osteoarthritis (OA) is a pathology characterized by the progressive erosion of articular cartilage, with concomitant structural and functional changes in the tissues around the joints. In this context, medicinal plants have become relevant tools in terms of their potential role in the prevention and treatment of OA, providing a safe and effective therapeutic or adjuvant approach. The aim of this study was to investigate the therapeutic efficacy of the ethyl acetate fraction of Bixa orellana leaves (BoEA) and ellagic acid (ElAc) for the therapeutic treatment of monosodium iodoacetate (MIA)-induced OA in rats. From the plant material, we obtained the crude extract by maceration with 70% hydroalcoholic solvent (BoHE), followed by fractionation with solvents in order of increasing polarity, obtaining the ethyl acetate (BoEA) fraction. The compound ElAc was identified and isolated in BoEA using high performance liquid chromatography (HPLC-PDA) and analytical curve. MIA-induced OA was performed on the right knee with a maximum volume of 2 mg/25 μL at the tibiopatellar femur joint, through the patellar ligament. All animals were previously sedated with ketamine hydrochloride® 10% (90 mg/kg) and then anesthetized using xylazine hydrochloride® 2% (5 mg/kg) in the intraperitoneal region. The doses of BoEA and ElAc compounds, as well as Indomethacin and sorbitol were performed via 12/12 hour gavage. Gavages were performed by administering a volume of 1 mL and adjusted according to the animal's weighing performed before the procedure. We evaluate the animals through clinical and radiological tests every 7 days. On the 29th day, euthanasia was performed by deep intraperitoneal anesthesia at a dosage of 0.3 ml of Xylazine (80mL/kg) + 0.3 ml of Ketamine (10mg/kg). All biological material was removed by puncture of the aorta, totaling 08-10 mL of blood in tubes containing EDTA. The results demonstrated that doses of the compounds BoEA and ElAc administered in the long term were capable of inducing anti- inflammatory and antinociceptive action evidenced through clinical tests and proved to be decisive in this process, inhibition evidenced by the decrease in serum levels of TNF-α and increase in IL -10 detected after 28 days of treatment. In relation to the radiological and histopathological images of the present study, we observed in the untreated group the presence of exuberant marginal osteophytes, subchondral bone sclerosis, areas of cartilage erosion and medial patellar dislocation, a case very different from the animals that were treated with phytochemical compounds, where they showed reduced progression of joint damage evidenced with lower degrees of joint changes. We concluded that the effects of BoEA and ElAc were able to reduce pain, inhibit the activity of catabolic pathways and consequently, inflammation through regulation and reciprocal balance of anti-inflammatory and pro-inflammatory cytokines in MIA-induced OA, in addition to attenuating the cartilage degeneration evidenced by radiological and histological images.